Editing of the HLA‐DR‐peptide repertoire by HLA‐DM. - Kropshofer, Harald; Vogt, Anne B.; Moldenhauer, Gerhard; Hammer, J.; Blum, J. S.; Hämmerling, Günter J. (The EMBO journal, 1996)
Antigenic peptide loading of classical major histocompatibility complex (MHC) class II molecules requires the exchange of the endogenous invariant chain fragment CLIP (class II associated Ii peptide) for peptides derived from antigenic proteins. This process is facilitated by the non‐classical MHC class II molecule HLA‐DM (DM) which catalyzes the removal of CLIP. Up to now it has been unclear whether DM releases self‐peptides other than CLIP and thereby modifies the peptide repertoire presented to T cells. Here we report that DM can release a variety of peptides from HLA‐DR molecules. DR molecules isolated from lymphoblastoid cell lines were found to carry a sizeable fraction of self‐peptides that are sensitive to the action of DM. The structural basis for this DM sensitivity was elucidated by high‐performance size exclusion chromatography and a novel mass spectrometry binding assay. The results demonstrate that the overall kinetic stability of a peptide bound to DR determines its sensitivity to removal by DM. We show that DM removes preferentially those peptides that contain at least one suboptimal side chain at one of their anchor positions or those that are shorter than 11 residues. These findings provide a rationale for the previously described ligand motifs and the minimal length requirements of naturally processed DR‐associated self‐peptides. Thus, in endosomal compartments, where peptide loading takes place, DM can function as a versatile peptide editor that selects for high‐stability MHC class II‐peptide complexes by kinetic proofreading before these complexes are presented to T cells.